Otoritas Gampong dalam Implementasi Syariat Islam di Aceh - Sulaiman Tripa (Sharia and Law Faculty, 2012)
According to formal judicial, Islamic law in Aceh was workable. The authority for the implementation of Islamic Shari’a is prevailed in government level: provincial, district/city as well as village. However, specific to village, the authority is very limited. This study tries to map the competency and authority of village in the implementation of Islamic law. The study was conducted with the doctrinal approach to the specification of normative studies, which used primary legal materials (legislation) and secondary legal materials (research). Data processing is done through interpretation (interpretative), while reports are prepared by exposure to descriptive. It can be concluded that village has limited authority in the implementation of Islamic law such: First, to form Wilayatul Hisbah at village level, the task is limited to admonish and advise. Second, the structure of village government and imuem geusyik meunasah has a duty and Shari’a obligation to prevent immoral activities. Third, the regulatory levels, the implementation of Islamic law is the material that can be applied to the provision of village level. Fourth, in the context of the completion of the case, some cases can be solved by the concept of Local Customary Court. Fifth, the village itself can form Baitul Mal at the village level. Village-owned limited authority as mentioned above is reasonable given the capabilities of settlement on the village level with the structures available, very modest compared to the above rule.